Composite positive electrode of aqueous zinc organic sulfur battery, preparation method of composite positive electrode and aqueous zinc organic sulfur battery

By using dibenzothiazole disulfide as the positive electrode active material, and by introducing a heterocyclic ring containing N and adjusting the π-conjugation plane, the problem of material collapse and dissolution in aqueous zinc ion batteries is solved, and high discharge voltage and cyclic stability is achieved, with important application prospects.

CN119601572AActive Publication Date: 2025-03-11ZHENGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411780828.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

In aqueous zinc ion batteries, the repeated embedding of Zn2+ can easily lead to collapse and dissolution of inorganic materials, resulting in poor electrochemical performance, and the synthesis of organic electrode materials based on quinone or amines is expensive and easy to soluble in aqueous solutions, resulting in a decrease in circulation capacity.

Method used

Dibenzothiazole disulfide is used as the positive electrode active material, and the bond dissociation energy of S-S bonds is reduced by introducing an N-containing heterocycle, the discharge voltage and reaction kinetics are improved, and low solubility and rapid charge transfer are achieved by adjusting the π-conjugation plane. At the same time, the weak coordination bond between N and Zn atoms is formed, so the solubility of the discharge product is reduced and the cycle stability of the battery is improved.

Benefits of technology

The excellent rate performance and cycle stability of the composite positive electrode of the aqueous zinc organic sulfur battery are achieved, with high discharge voltage and low overpotential, and still have good electrochemical performance under high load, which has important application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005172744160000011
    Figure HDA0005172744160000011
  • Figure HDA0005172744160000012
    Figure HDA0005172744160000012
  • Figure HDA0005172744160000021
    Figure HDA0005172744160000021
Patent Text Reader

Abstract

The invention discloses a composite positive electrode of an aqueous zinc organic sulfur battery, a preparation method of the composite positive electrode and the aqueous zinc organic sulfur battery, and belongs to the technical field of aqueous zinc ion batteries. The aqueous zinc organic sulfur battery composite positive electrode sequentially comprises a current collector, an organic sulfur dry-type electrode and an electrolyte storage device, and the organic sulfur dry-type electrode is prepared from dibenzothiazyl disulfide, a conductive agent and a binder under the solvent-free condition through a dry rolling technology. According to the invention, dibenzothiazyl disulfide is used as an aqueous zinc organic sulfur positive electrode active material, and due to rapid molecular dynamics and low solubility, the material shows excellent rate capability and cycling stability, also has high discharge voltage and low overpotential, still has good electrochemical performance under high load, and has important application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to an aqueous zinc-organic sulfur battery composite positive electrode and a preparation method thereof, and an aqueous zinc-organic sulfur battery. Background Art

[0002] With the progress of modernization, energy consumption continues to rise sharply. In this context, the development of clean energy storage and conversion technologies has been considered a major task for human society. Among all commercial electrochemical energy storage devices, lithium-ion batteries have attracted widespread attention due to their high energy density and long cycle life. However, limited lithium resources, toxic organic electrolytes, and potential safety hazards have hindered their further application in large-scale energy storage. Among energy storage systems other than lithium-ion batteries, aqueous zinc-ion batteries show potential for application in large-scale energy storage due to their high zinc abundance and non-toxic aqueous electrolytes.

[0003] Currently, many inorganic cathode materials have been used in aqueous zinc-ion batteries. 2+ Repeated embedding of organic materials can easily cause the collapse and dissolution of inorganic materials, resulting in poor electrochemical performance. In contrast, the storage and release of multivalent ions in organic cathode materials are achieved through reversible coordination reactions of active functional groups, and their internal space is adjustable to accommodate large-sized carriers. In addition, organic electrode materials have the advantages of low cost, environmental friendliness, and abundant raw material sources, which meet the requirements of human sustainable development.

[0004] However, in aqueous zinc-ion batteries, organic electrode materials based on quinones or amines are expensive to synthesize and are easily soluble in aqueous solutions, resulting in a decrease in the battery's cycle capacity. Small molecule organic sulfides based on SS bonds have been a hot topic of research as a common, economical and environmentally friendly organic cathode material. The electronegativity of sulfur (2.58) is lower than that of oxygen and nitrogen (3.44 and 3.04, respectively), and its interaction with hydrogen in water is weak, and its hydrophilicity in aqueous solution is low. Therefore, even without polymerization or grafting with hydrophobic groups, most small organic sulfide molecules show low solubility in aqueous solution. However, in aqueous solution, the dissociation and recombination of SS bonds cause large internal reorganization energy and produce extremely high reaction energy barriers, which significantly reduce the discharge potential and reaction kinetics. Summary of the invention

[0005] The present invention aims to provide an aqueous zinc-organic sulfur battery composite positive electrode and a preparation method thereof and an aqueous zinc-organic sulfur battery. The aqueous zinc-organic sulfur battery composite positive electrode has excellent rate performance and cycle stability, high discharge voltage and low overpotential, and still has good electrochemical performance under high load, and has important application prospects.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] Provided is an aqueous zinc-organic sulfur battery composite positive electrode, which comprises a current collector, an organic sulfur dry electrode and an electrolyte storage in sequence, wherein:

[0008] The organic sulfur dry electrode is prepared by using a dry rolling technology to press dibenzothiazole disulfide, a conductive agent and a binder under solvent-free conditions.

[0009] The present invention uses dibenzothiazole disulfide as the positive electrode active material. On the one hand, the bond dissociation energy of the SS bond is reduced by introducing a N-containing heterocyclic ring, which greatly increases the discharge voltage and improves the reaction kinetics. At the same time, the π-conjugated plane is adjusted to achieve low solubility and rapid charge transfer. In addition, due to the adjacent active sites and Zn 2+ Due to the synergistic effect between the N and Zn atoms, a weak coordination bond (i.e., N—Zn—S bond) is formed between the N and Zn atoms, which reduces the solubility of the discharge products and thus improves the cycle stability of the battery.

[0010] According to the above scheme, the organic sulfur dry electrode is prepared by mixing and grinding dibenzothiazole disulfide and a conductive agent, adding a binder, and then, under the action of shear force, the binder is fiberized to bind the powder into a block, and the organic sulfur dry electrode is obtained by rolling.

[0011] Preferably, the grinding time is ≥ 20 min.

[0012] Preferably, the rolling time is ≥10 min.

[0013] According to the above scheme, the mass ratio of dibenzothiazole disulfide, conductive agent and binder is (30-70):(25-69):(1-5).

[0014] According to the above scheme, the conductive agent is selected from one or a combination of acetylene black (AB), Super P, Ketjen black (KB), single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0015] According to the above scheme, the binder is one or a combination of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR).

[0016] According to the above scheme, the current collector is a titanium mesh or a stainless steel mesh, and its size should be larger than that of the dry positive electrode, so that the full dry positive electrode membrane can be better attached to the current collector.

[0017] According to the above scheme, the electrolyte reservoir is a polymer with a porous structure, a ceramic coating material, an inorganic material, a carbon-based material or some functional polymers.

[0018] According to the above scheme, the loading amount of the positive electrode active material is 2.0-20 mg cm -2 .

[0019] Provided is a method for preparing the aqueous zinc-organic sulfur composite positive electrode, comprising the following steps: rolling and compounding an organic sulfur dry electrode on a current collector, and then rolling an electrolyte reservoir on the organic sulfur dry electrode to obtain an aqueous zinc-organic sulfur composite positive electrode.

[0020] Provided is an aqueous zinc-organic sulfur battery, comprising the aqueous zinc-organic sulfur composite positive electrode.

[0021] According to the above scheme, the battery also includes a negative electrode, an electrolyte and a separator.

[0022] Preferably, the negative electrode is a zinc sheet.

[0023] Preferably, the electrolyte is one or more of a zinc trifluoromethanesulfonate solution or a zinc sulfate solution.

[0024] Preferably, the concentration of the electrolyte is 2-3 mol L -1 .

[0025] Preferably, the diaphragm is one or more of glass fiber membrane GF / A and glass fiber membrane GF / D.

[0026] According to the above scheme, the zinc-organic sulfur battery is prepared and allowed to stand for 3-12 hours before use.

[0027] The beneficial effects of the present invention are as follows:

[0028] 1. The present invention provides a composite positive electrode for an aqueous zinc-organic sulfur battery, using dibenzothiazole disulfide as the positive electrode active material. Due to its fast molecular dynamics and low solubility, it exhibits excellent rate performance and cycle stability. -1 After 1000 cycles, the capacity retention rate is still 95.7%; at the same time, it also has a low overpotential and excellent comprehensive electrochemical performance, and has important application prospects.

[0029] 2. The positive electrode of the present invention is used in aqueous zinc ion batteries and has a relative 2+ The voltage is about 1.02 V, which is higher than most reported n-type materials.

[0030] 3. The present invention adopts a dry method to prepare the positive electrode sheet, which is conducive to achieving a high load of the positive electrode active material. With the high ionic conductivity of the aqueous electrolyte, the obtained zinc-organic sulfur battery still has good electrochemical performance even under high positive electrode load; wherein: the loading amount is 10.2 mg cm at a current density of 1C -2 The organic sulfide can still maintain 129.8 mAhg after 50 cycles -1At the same time, the cathode preparation process does not require heating and solvent participation, the method is simpler and more feasible, with low cost, which is conducive to industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used together with Example 1 of the present invention to explain the present invention and do not constitute a limitation of the present invention.

[0032] Figure 1 The figure is a flow chart of the preparation of the electrode sheet of the zinc-organic sulfur battery in the embodiment of the present invention.

[0033] Figure 2 The loading amount is 10.2 mg cm in Example 2. -2 MBTS dry electrode at 0.16Ag -1 Cycling performance diagram at different current densities.

[0034] Figure 3 When MBTS, DPDS and DPyDS are selected as the organic sulfur active materials in Example 1 and Comparative Examples 1-2, respectively, at 1Ag -1 Cycling performance diagram at different current densities.

[0035] Figure 4 When different organic sulfur active materials are selected in Example 1 and Comparative Examples 1-4, the -1 The redox potential and overpotential values.

[0036] Figure 5 The rate performance test is performed when MBTS and DPDS are selected as the organic sulfur active materials in Example 1 and Comparative Example 1, respectively.

[0037] Figure 6 UV-visible spectra of the organic sulfur active materials MBTS, DPDS and DPyDS selected in Example 1 and Comparative Examples 1-2 in 1MZn(OTF)2 aqueous solution. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0039] Example 1

[0040] This embodiment provides a composite positive electrode for an aqueous zinc-organic sulfur battery, such as Figure 1 As shown, the following steps are included:

[0041] 1) The organic sulfur active material dibenzothiazole disulfide MBTS and Ketjen black are preliminarily mixed in a mass ratio of 1:1, and the resulting mixture is fully ground in a small mortar for 20 minutes to mix evenly to obtain a mixed powder; then the mixed powder and the binder polytetrafluoroethylene are mixed in a small mortar in a mass ratio of 95:5, and under the action of shear force, the polytetrafluoroethylene binder is fibrillated to bond the mixed powder into an electrode blank, and the electrode is repeatedly rolled in the mortar for 15 minutes. After rolling, the thickness of the electrode sheet is about 0.09 mm, and the electrode blank is cut into a circular electrode sheet with a diameter of 6 mm using a puncher to obtain an organic sulfur dry electrode.

[0042] 2) The organic sulfur dry electrode was then rolled onto the titanium mesh, and finally the porous carbon-based material layer was rolled onto the organic sulfur dry electrode to form a zinc-organic sulfur battery composite positive electrode. The loading amount of the organic sulfur active substance in the obtained electrode was 2.5 mg cm -2 about.

[0043] Battery assembly: The zinc-organic sulfur battery is assembled in the order of positive electrode, separator, electrolyte and negative electrode. The separator is glass fiber membrane GF / A, and the electrolyte is 100 μl of 2 mol L -1 The aqueous solution of zinc trifluoromethanesulfonate was used to fully wet the positive electrode sheet, and the negative electrode was a polished zinc sheet with a diameter of 14 mm. After assembling the button cell, its electrochemical performance was tested.

[0044] Electrochemical performance test: All battery assemblies were completed in air at room temperature. Constant current charge and discharge tests and long cycle tests of button cells were achieved using CT2001A LAND, with a test voltage window of 0.2-1.6V.

[0045] Example 2

[0046] The specific steps are the same as those in Example 1, except that the thickness of the electrode sheet after rolling is about 0.43 mm, and the loading amount of the organic sulfur active substance is 10.2 mg cm -2 .

[0047] Comparative Example 1

[0048] The specific steps are the same as those in Example 1, except that diphenyl disulfide DPDS is selected as the organic sulfur active material.

[0049] Comparative Example 2

[0050] The specific steps are the same as those in Example 1, except that the organic sulfur active material is dipyridyl disulfide DPyDS.

[0051] Comparative Example 3

[0052] The specific steps are the same as those in Example 1, except that 4,4'-dimethoxydiphenyl disulfide MeODPDS is selected as the organic sulfur active material.

[0053] Comparative Example 4

[0054] The specific steps are the same as those in Example 1, except that the organic sulfur active material is 4-[(4-cyanophenyl)disulfide]benzonitrile CNDPDS.

[0055] like Figure 2 As shown, it is the loading amount of 10.2 mg cm in Example 2 -2 The MBTS-containing zinc-organic sulfur battery composite cathode is 0.16A g -1 The cycling performance at a current density of 1.28 mAh g can still be maintained at 129.8 mAh g after 50 cycles. -1 The specific capacity and capacity retention rate were 93.6%, which proved the feasibility of preparing aqueous zinc-organic sulfur composite positive electrode.

[0056] like Figure 3 As shown, at 1Ag -1 The long-term cycle stability of three zinc-organic sulfur batteries, namely, comparative example 1 (MBTS), comparative example 1 (DPDS) and comparative example 2 (DPyDS), was tested under the following conditions. The MBTS-containing battery in example 1 was -1 After 1000 cycles, the battery still maintains 112.0 mAh g -1 The reversible specific capacity of the battery in Comparative Example 2 is 95.7%, and the corresponding capacity retention rate is 95.7%. In contrast, although the DPyDS battery in Comparative Example 2 has a higher initial specific capacity, it has a serious capacity decay due to its high solubility, and the capacity retention rate is only 40.1% after 1000 cycles; while the DPDS battery in Comparative Example 1 has good cycle stability after 500 cycles, but its rate performance is very poor, at 1Ag -1 It shows 58.9mAh g -1 Low specific capacity.

[0057] like Figure 4 and Figure 5 As shown in the figure, compared with other common organic disulfides, the MBTS battery in Example 1 has the highest discharge voltage of 1.02V and the lowest redox potential difference of 100mV, showing the excellent electrochemical performance of MBTS that is different from other organic sulfur molecules. Compared with the classic organic sulfur molecule DPDS in Comparative Example 1, the MBTS battery not only increases the discharge voltage by 0.8V, but also significantly reduces the overpotential, showing faster kinetic characteristics. Compared with the DPDS battery in Comparative Example 1, it has a higher discharge voltage at 2A g -1 Still has 98.9mAh g -1 The specific capacity shows better rate performance.

[0058] like Figure 6As shown in the figure, the solubility of three organic sulfurs, MBTS, DPDS and DPyDS, in 1MZn(OTF)2 was determined by UV-visible spectroscopy. The concentrations of DPDS, DPyDS and MBTS in the solution were 0.012, 0.656 and 0.006 mmol L -1 , indicating that MBTS has the lowest solubility in the electrolyte.

[0059] The above results show that the zinc-organic sulfur battery cathode material provided by the present invention has the advantages of high voltage, fast reaction kinetics, low solubility, etc., which solves the problems of slow kinetics and low discharge voltage of organic sulfur cathode in water system. Combined with the dry electrode sheet preparation method, the organic sulfur electrode still has good cycle stability under high load.

[0060] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A composite positive electrode for an aqueous zinc-organic sulfur battery, characterized in that: The invention comprises a current collector, an organic sulfur dry electrode and an electrolyte reservoir in sequence, wherein: The organic sulfur dry electrode is prepared by using a dry rolling technology to press dibenzothiazole disulfide, a conductive agent and a binder under solvent-free conditions.

2. The aqueous zinc-organic sulfur battery composite positive electrode according to claim 1, characterized in that: The organic sulfur dry electrode is prepared by mixing and grinding dibenzothiazole disulfide and a conductive agent, adding a binder, and then fibrillating the binder under the action of shear force to bind the powder into a block, and then rolling to obtain the organic sulfur dry electrode.

3. The aqueous zinc-organic sulfur battery composite positive electrode according to claim 2, characterized in that: Grinding time ≥ 20min; rolling time ≥ 10min.

4. The aqueous zinc-organic sulfur battery composite positive electrode according to claim 1, characterized in that: The mass ratio of dibenzothiazole disulfide, conductive agent and binder is (30-70):(25-69):(1-5).

5. The aqueous zinc-organic sulfur battery composite positive electrode according to claim 1, characterized in that: The conductive agent is selected from one or a combination of acetylene black, Super P, Ketjen black, single-walled carbon nanotubes and multi-walled carbon nanotubes; the binder is one or a combination of polytetrafluoroethylene, polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber; the current collector is a titanium mesh or a stainless steel mesh; the electrolyte reservoir is a polymer with a porous structure, a ceramic coating material, an inorganic material, a carbon-based material or some functional polymers.

6. The aqueous zinc-organic sulfur battery composite positive electrode according to claim 1, characterized in that: The loading amount of the positive electrode active material is 2.0 to 20 mg cm -2 .

7. A method for preparing an aqueous zinc-organic sulfur composite positive electrode according to any one of claims 1 to 6, characterized in that: The following steps are involved: The organic sulfur dry electrode is rolled and composited on the current collector, and then the electrolyte reservoir is rolled and pressed on the organic sulfur dry electrode to obtain an aqueous zinc organic sulfur composite positive electrode.

8. An aqueous zinc-organic sulfur battery, characterized in that: It comprises the aqueous zinc-organic sulfur composite positive electrode as described in any one of claims 1-6.

9. The aqueous zinc-organic sulfur battery according to claim 8, characterized in that: The battery also includes a negative electrode, an electrolyte and a separator.

10. The aqueous zinc-organic sulfur battery according to claim 9, characterized in that: The electrolyte is one or more of a zinc trifluoromethanesulfonate solution or a zinc sulfate solution; the concentration of the electrolyte is 2-3 mol L -1 .

Citation Information

Patent Citations

  • Sulfhydryl compound carbon nanotube composite positive electrode and secondary aluminium battery

    CN104078654A

  • Method for producing organo-sulfur electrode active material

    CN111226333A

  • Mesoporous carbon confinement ether organic positive electrode active material for aqueous zinc battery and preparation method and application of mesoporous carbon confinement ether organic positive electrode active material

    CN116864654A

  • Energy storage device material from heterocyclic organic sulfur compounds and method of designing it

    US20040157122A1